Method for producing electromagnetic wave shielding sheet and electromagnetic wave shielding sheet
By using a dispersion of carbon nanotubes, inorganic pigments, sodium carboxymethylcellulose and water in the manufacturing method of electromagnetic wave shielding sheets, and controlling the ratio of inorganic pigments, the problem of high cost of electromagnetic wave shielding sheets in the prior art is solved, and the effect of high shielding and low cost is achieved.
Patent Information
- Application Number
- CN202180026782.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-01
- Filing Date
- 2021-02-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-02-01
AI Technical Summary
Compared with inorganic pigments, carbon nanotubes are more expensive, and the prior art is difficult to ensure electromagnetic wave shielding while reducing costs.
By making a dispersion containing carbon nanotubes, inorganic pigments, sodium carboxymethylcellulose and water, and after drying, an electromagnetic wave shielding sheet is controlled to be more than 1/4 and less than 1/4 of the mass ratio of the inorganic pigments to the mass ratio of the carbon nanotubes.
High shielding properties of electromagnetic waves and low-cost electromagnetic wave shielding sheets are achieved, reducing the use of carbon nanotubes, thereby reducing production costs.
Smart Images

Figure CN115428601B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing an electromagnetic wave shielding sheet and the electromagnetic wave shielding sheet. Background Art
[0002] Carbon nanotubes have a structure like a uniform graphite plane rolled into a tube. Both ends of the carbon nanotube are closed with a structure like a hemisphere of fullerene, and each has six five-membered rings. Because carbon nanotubes have this unique structure, they have various properties and are expected to be used in a wide range of fields.
[0003] For example, Patent Document 1 describes the production of an electromagnetic wave shielding sheet from a carbon nanotube aqueous dispersion containing a polysaccharide such as carboxymethyl cellulose and an anionic surfactant as a dispersant.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-82610 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] The above-mentioned carbon nanotubes are more expensive than inorganic pigments. Therefore, if a part of the carbon nanotubes can be replaced with inorganic pigments while ensuring the shielding property against electromagnetic waves, an electromagnetic shielding sheet can be manufactured at low cost.
[0009] One of the purposes of some aspects of the present invention is to provide a method for manufacturing an electromagnetic wave shielding sheet having high shielding performance against electromagnetic waves and low cost. Another purpose of some aspects of the present invention is to provide an electromagnetic wave shielding sheet having high shielding performance against electromagnetic waves and low cost.
[0010] Solutions for solving problems
[0011] One embodiment of a method for producing an electromagnetic shielding sheet of the present invention comprises:
[0012] A step of preparing a dispersion containing carbon nanotubes, an inorganic pigment, sodium carboxymethyl cellulose and water; and
[0013] a step of drying the dispersion,
[0014] In the dispersion, a ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes is 1 / 4 or more and 1 or less.
[0015] In one embodiment of the method for manufacturing the electromagnetic wave shielding sheet,
[0016] The inorganic pigment is kaolin.
[0017] In any one embodiment of the method for manufacturing the electromagnetic wave shielding sheet,
[0018] In the dispersion, a ratio of the mass of the sodium carboxymethyl cellulose to the sum of the mass of the carbon nanotubes and the mass of the inorganic pigment is 3 or less.
[0019] In any one embodiment of the method for manufacturing the electromagnetic wave shielding sheet,
[0020] In the process of preparing the dispersion, only the sodium carboxymethyl cellulose is used as a dispersant.
[0021] In any one embodiment of the method for manufacturing the electromagnetic wave shielding sheet,
[0022] The process of preparing the dispersion comprises:
[0023] A step of mixing the carbon nanotubes, the sodium carboxymethyl cellulose and the water to prepare a mixed solution; and
[0024] A step of dispersing the carbon nanotubes contained in the mixed solution by a counter-collision method in water.
[0025] One embodiment of the electromagnetic shielding sheet of the present invention
[0026] Contains carbon nanotubes, inorganic pigments and sodium carboxymethyl cellulose.
[0027] The ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes is 1 / 4 or more and 1 or less.
[0028] In one embodiment of the electromagnetic wave shielding sheet,
[0029] The inorganic pigment is kaolin.
[0030] In any one of the embodiments of the electromagnetic wave shielding sheet,
[0031] The ratio of the mass of the sodium carboxymethyl cellulose to the sum of the mass of the carbon nanotubes and the mass of the inorganic pigment is 3 or less.
[0032] Effects of the Invention
[0033] According to the method for producing an electromagnetic shielding sheet of the present invention, an electromagnetic shielding sheet having high shielding properties against electromagnetic waves and low cost can be produced. In addition, the electromagnetic shielding sheet of the present invention can have high shielding properties against electromagnetic waves and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a flowchart for explaining the method for producing the electromagnetic shielding sheet according to the present embodiment.
[0035] Figure 2 This is a table for explaining the inorganic pigments used in the experimental examples.
[0036] Figure 3 This is a table showing the evaluation results of the electromagnetic wave shielding properties of coated papers.
[0037] Figure 4 This is a table showing the evaluation results of the electromagnetic wave shielding properties of the dry films.
[0038] Figure 5 This is a graph showing the relationship between the ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes and “S21” when kaolin is used as the inorganic pigment.
[0039] Figure 6 This is a graph showing the relationship between the ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes and “S21” when kaolin is used as the inorganic pigment.
[0040] Figure 7 This is a graph showing the relationship between the ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes and “S21” when light calcium carbonate is used as the inorganic pigment.
[0041] Figure 8 This is a graph showing the relationship between the ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes and “S21” when light calcium carbonate is used as the inorganic pigment.
[0042] Fig. 9 This is a graph showing the relationship between the ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes and “S21” when heavy calcium carbonate is used as the inorganic pigment.
[0043] Fig.10 This is a graph showing the relationship between the ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes and “S21” when heavy calcium carbonate is used as the inorganic pigment.
[0044] Fig.11 This is a table showing the evaluation results of the dispersibility of dispersions 1 to 12.
[0045] Fig.12 These are photographs showing the state of dispersions 1 to 12 after being dried overnight.
[0046] Fig.13This is a table showing the evaluation results of the electromagnetic wave shielding properties when the ratio of carbon nanotubes to sodium carboxymethylcellulose was changed.
[0047] Fig.14 is a graph showing “S21” with respect to frequency.
[0048] Fig.15 is a graph showing “S21” with respect to frequency.
[0049] Fig.16 This is a table showing the evaluation results of the electromagnetic wave shielding properties when the number of passes was changed.
[0050] Fig.17 is a graph showing “S21” with respect to frequency.
[0051] Fig.18 is a graph showing “S21” with respect to frequency.
[0052] Fig.19 This is a table showing the evaluation results of the electromagnetic wave noise suppression performance of coated paper.
[0053] Fig. 20 This is a graph showing “Rtp” with respect to frequency when the ratio of the inorganic pigment to the carbon nanotube is 0.25.
[0054] Fig.21 This is a graph showing “Rtp” with respect to frequency when the ratio of the inorganic pigment to the carbon nanotube is 0.5.
[0055] Fig. 22 This is a graph showing “Rtp” with respect to frequency when the ratio of the inorganic pigment to the carbon nanotube is 1.0.
[0056] Fig.23 This is a graph showing “Rtp” with respect to frequency when the ratio of the inorganic pigment to the carbon nanotube is 2.0.
[0057] Fig.24 This is a graph showing “Rtp” with respect to frequency when the ratio of the inorganic pigment to the carbon nanotube is 3.0.
[0058] Fig.25 This is a graph showing “Rtp” with respect to frequency when the ratio of the inorganic pigment to the carbon nanotube is 4.0. DETAILED DESCRIPTION
[0059] Hereinafter, preferred embodiments of the present invention will be described in detail using the accompanying drawings. Moreover, the embodiments described below are not intended to unduly limit the contents of the present invention as described in the claims. In addition, all the structures described below are not necessarily essential components of the present invention.
[0060] 1. Method for manufacturing electromagnetic wave shielding sheet
[0061] First, a method for producing an electromagnetic shielding sheet according to the present embodiment will be described with reference to the drawings. Figure 1 This is a flowchart for explaining the method for producing the electromagnetic shielding sheet according to the present embodiment.
[0062] The method for manufacturing an electromagnetic wave shielding sheet of the present embodiment includes: a dispersion liquid preparation step of preparing a dispersion liquid containing carbon nanotubes (hereinafter, also referred to as "CNT"), an inorganic pigment, sodium carboxymethyl cellulose (hereinafter, also referred to as "CMC"), and water. Figure 1 As shown, the dispersion liquid preparation process includes, for example: a mixed liquid preparation process (step S1), mixing CNT, CMC and water to prepare a mixed liquid; a dispersion process (step S2), dispersing the CNT contained in the mixed liquid by a counter-collision method in water; and an inorganic pigment mixing process (step S3), mixing an inorganic pigment into the dispersion liquid. In addition, the manufacturing method of the electromagnetic wave shielding sheet of this embodiment includes a drying process (step S4) of drying the dispersion liquid. Below, each process of the manufacturing method of the electromagnetic wave shielding sheet of this embodiment is described in sequence.
[0063] 1.1. Mixed solution preparation process (step S1)
[0064] 1.1.1. Carbon nanotubes (CNT)
[0065] As CNTs used in the mixed solution preparation process, there can be mentioned single-walled carbon nanotubes (SWNTs) formed by rolling a six-membered ring network (graphene sheet) made of carbon into a cylindrical shape, and multi-walled carbon nanotubes (MWNTs) formed by rolling a plurality of graphene sheets into concentric circles. In the mixed solution preparation process, only one of SWNTs and MWNTs can be used, or both can be used. However, considering the dispersibility of CNTs, it is preferred to use only MWNTs as CNTs.
[0066] The CNTs described above are produced into a preferred size by, for example, arc discharge, laser ablation, CVD (Chemical Vapor Deposition), etc. The CNTs used in the mixed solution production step may be produced by any method.
[0067] The diameter of CNT is not particularly limited, but is preferably 1 nm or more and 100 nm or less, more preferably 5 nm or more and 50 nm or less, and further preferably 8 nm or more and 15 nm or less. If the diameter of CNT is within the above range, a dispersion with good dispersibility can be prepared. The diameter of CNT can be measured by SEM (Scanning Electron Microscope: Scanning Electron Microscope).
[0068] The fiber length of CNT is not particularly limited, but is preferably 0.5 μm or more and 50 μm or less, and more preferably 15 μm or more and 35 μm or less. If the fiber length of CNT is within the above range, a dispersion with good dispersibility can be prepared. The fiber length of CNT can be measured by SEM. In addition, the so-called "fiber length of CNT" is the length of CNT in a state of being bundled (bundled) due to van der Waals force, and is the length of CNT before being dispersed into the solvent.
[0069] The BET specific surface area of CNT is not particularly limited, but is preferably 50 m 2 / g or more, 500m 2 / g or less, more preferably 100m / g 2 / g or more, 300m 2 / g or less. If the BET specific surface area of CNT is within the above range, a dispersion with good dispersibility can be prepared. In addition, the so-called "BET specific surface area" is a specific surface area measured by the BET (Brunauer Emmett Teller) method, which can be measured by an automatic specific surface area measuring device.
[0070] In the mixed solution, the content of CNT is not particularly limited, but is preferably 0.1% by mass or more and 10.0% by mass or less, more preferably 0.5% by mass or more and 5.0% by mass or less, and further preferably 1.0% by mass or more and 3.0% by mass or less. If the content of CNT is 0.1% by mass or more, an electromagnetic wave shielding sheet with high electromagnetic wave shielding (electromagnetic wave shielding) can be manufactured. Moreover, if the content of CNT is 5.0% by mass or less, a dispersion with good dispersibility can be prepared.
[0071] 1.1.2. Sodium carboxymethyl cellulose (CMC)
[0072] In the mixed solution preparation step, CMC is used as a dispersant. Here, the term "dispersant" refers to an additive that disperses CNTs in water and helps prevent CNTs from agglomerating and settling.
[0073] In the mixed solution preparation process, it is preferred to use only CMC as a dispersant. That is, the mixed solution prepared in the mixed solution preparation process preferably does not contain additives that help prevent the aggregation and sedimentation of CNTs except CMC. By using only CMC as a dispersant, for example, compared with the case where an anionic surfactant is added as a dispersant in addition to CMC, it is possible to prevent the mixing of bubbles, etc., so that the mixed solution can be easily prepared, and an electromagnetic wave shielding sheet without bubble mixing can be manufactured in the drying process described later.
[0074] The weight average molecular weight of CMC is not particularly limited, but is preferably more than 5000 and less than 100000, more preferably more than 10000 and less than 60000, and further preferably more than 10000 and less than 35000. If the weight average molecular weight of CMC is more than 5000, CMC is easy to entangle with CNT, and the dispersibility of CNT is improved. However, if the weight average molecular weight is too large, the dispersibility will deteriorate instead, so it is preferred that the molecular weight of CMC is less than 100000. In addition, the "weight average molecular weight" in this specification refers to the weight average molecular weight of polystyrene conversion measured by gel permeation chromatography (GPC).
[0075] The degree of etherification of CMC is not particularly limited, but is preferably 0.6 or more and 1.2 or less, and more preferably 0.6 or more and 0.8 or less. When the degree of etherification of CMC is within the above range, a dispersion having good dispersibility can be prepared.
[0076] The content of CMC in the mixed liquid is not particularly limited, but is preferably 0.1 mass % to 10.0 mass %, more preferably 0.5 mass % to 5.0 mass %, and further preferably 1.0 mass % to 3.0 mass %.
[0077] In the mixed liquid, the mass of CMC is M CMC Relative to the sum of the mass of CNT and inorganic pigments M SUM M CMC / M SUM Preferably it is 1 / 7 or more, more preferably 1 / 6 or more. CMC / M SUM When the ratio is 1 / 7 or more, a dispersion liquid with good dispersibility can be prepared (for details, refer to "3. Experimental Examples" described later).
[0078] In the mixed solution, the ratio of M CMC / M SUM Preferably it is 3 or less, more preferably 1 or less. CMC / M SUM When the ratio is 3 or less, an electromagnetic shielding sheet having high electromagnetic shielding properties can be produced (for details, refer to "3. Experimental Examples" described later).
[0079] 1.1.3. Water
[0080] In the mixed solution preparation process, water is used as a solvent. As water, for example, pure water such as ion exchange water, ultrafiltration water, reverse osmosis water and distilled water, and water such as ultrapure water that has removed ionic impurities as much as possible can be cited. By using water as a solvent, an environmentally friendly mixed solution can be prepared compared to the case where an organic solvent is used as a solvent. In the mixed solution preparation process, CNT, CMC and water can also be mixed to prepare a mixed solution. That is, the mixed solution can also contain only CNT, CMC and water.
[0081] 1.2. Dispersion process (step S2)
[0082] In the dispersion process, the CNT contained in the mixed solution is dispersed by the opposite collision method in water. By utilizing the opposite collision method in water to disperse the CNT contained in the mixed solution, even if the mixed solution contains only CMC as a dispersant, the CNT can be dispersed with good dispersibility. Thus, a dispersion with good dispersibility can be prepared.
[0083] In the "in-water counter-collision method" of the present embodiment, a mixed liquid containing CNTs is ejected at high pressure from a pair of nozzle holes (a first nozzle hole and a second nozzle hole) arranged opposite to each other, and the mixed liquid ejected from the first nozzle hole is caused to collide with the mixed liquid ejected from the second nozzle hole to disperse the CNTs. Preferably, in the in-water counter-collision method, the CNTs contained in the mixed liquid ejected from the first nozzle hole are caused to collide with the CNTs contained in the mixed liquid ejected from the second nozzle hole to disperse the CNTs. In the in-water counter-collision method, as long as the central axis of the first nozzle hole and the central axis of the second nozzle hole intersect with each other, the two central axes may be on a straight line or may be inclined to each other.
[0084] In the water collision method in the dispersion step, the mixed liquid is ejected from a nozzle hole having a diameter of preferably 50 μm or more and 200 μm or less, more preferably 80 μm or more and 120 μm or less, and further preferably 100 μm, so that the mixed liquids collide with each other. If the diameter of the nozzle hole is 50 μm or more, even a mixed liquid with high viscosity can be ejected from the nozzle hole. Furthermore, if the diameter of the nozzle hole is 200 μm or less, the collision energy between the mixed liquids can be increased.
[0085] In the water facing collision method of the dispersion process, the mixed solution is ejected at a pressure of preferably more than 150MPa, less than 250MPa, more preferably more than 180MPa, less than 220MPa, and more preferably 200MPa, so that the mixed solutions collide with each other. If the pressure is more than 150MPa, the collision energy between the mixed solutions can be increased. And, if the pressure is less than 250MPa, the following situation can be suppressed: the collision energy is too high and the fiber of CNT is disconnected, causing the viscosity of the dispersion to decrease.
[0086] Specifically, the underwater collision method of the dispersion process is performed using a wet micronizer "Star Burst Labo" (model name: HJP-25005) manufactured by Sugino Machinery Co., Ltd. This wet micronizer has a high energy density compared to, for example, an ultrasonic homogenizer and a ball mill, and can produce a dispersion with good dispersibility in a short time. In addition, this wet micronizer can minimize the mixing of impurities and can produce a dispersion with very few impurities.
[0087] The number of passes of the mixed solution in the wet micronizing device is preferably more than 1 time and less than 40 times, more preferably more than 2 times and less than 10 times, and further preferably 2 times or 3 times. If the number of passes is less than 40 times, the following situation can be suppressed: the fibers of CNT are disconnected due to the collision of the mixed solution with each other, resulting in a lower viscosity of the dispersion. In addition, if the number of passes is more than 2 times, the CNT can be well dispersed uniformly. Moreover, if the number of passes is more than 2 times, no significant difference is confirmed in the shielding of electromagnetic waves. Therefore, if the number of passes is more than 2 times and less than 10 times, both dispersibility and electromagnetic wave shielding can be guaranteed, and the processing time of the wet micronizing device can be shortened.
[0088] Here, the so-called "number of times the mixed liquid passes through the wet micronizing device" is the number of times the mixed liquid circulates in the wet micronizing device. For example, the so-called "number of times" means that the CNTs that have collided once collide again so that the mixed liquid circulates twice. In this way, the number of times the mixed liquid passes is equivalent to the number of collisions of the CNTs contained in the mixed liquid. In addition, the number of times the mixed liquid passes is proportional to the processing time of the wet micronizing device. If the processing time of the wet micronizing device is long, the number of times the mixed liquid circulates increases.
[0089] In addition, the device used in the underwater collision method in the dispersion process is not limited to the above-mentioned wet micronization device "StarBurst Labo" as long as it can produce a dispersion with good dispersibility and produce an electromagnetic wave shielding sheet with high electromagnetic wave shielding properties. In addition, the underwater collision method may not be used in the dispersion process, as long as it can produce a dispersion with good dispersibility and produce an electromagnetic wave shielding sheet with high electromagnetic wave shielding properties.
[0090] In addition, it is preferred that the mixed solution is treated by a homogenizer as a pretreatment before the dispersion process. The homogenizer may be an ultrasonic type that causes cavitation by ultrasound, a stirring type that stirs the mixed solution, or a pressure type that applies pressure to the mixed solution. By treating with a homogenizer, the aggregates formed by CNTs can be reduced, and the dispersion process can be smoothly performed.
[0091] 1.3. Inorganic pigment mixing process (step S3)
[0092] In the inorganic pigment mixing step, the inorganic pigment is mixed into the dispersion prepared in the dispersion step to prepare a dispersion containing CNT, inorganic pigment, CMC and water. The mixing method of the inorganic pigment is not particularly limited, and for example, a homogenizer is used as in the pretreatment of the dispersion step. Inorganic pigment refers to inorganic pigments in chemistry, and is a pigment made of oxides obtained from natural ores or metals through chemical reactions.
[0093] The inorganic pigment is preferably kaolin. When the inorganic pigment is kaolin, the electromagnetic shielding property of the electromagnetic shielding sheet tends to be higher than when the inorganic pigment is light calcium carbonate or heavy calcium carbonate (for details, refer to "3. Experimental Examples" described later).
[0094] In the dispersion prepared by the inorganic pigment mixing step, the mass M of the inorganic pigment is COL Relative mass of CNT M CNT M COL / M CNT is greater than 1 / 4 and less than 1, preferably greater than 1 / 4 and less than 1 / 2. COL / M CNT If the ratio of CNT is 1 / 4 or more, the ratio of CNT is small, so that a low-cost electromagnetic wave shielding sheet can be manufactured. COL / M CNT When the ratio M is less than 1, an electromagnetic shielding sheet with high electromagnetic shielding properties can be manufactured. COL / M CNT When it is greater than 1, the ratio of CNTs becomes too small, and the electromagnetic shielding property becomes low (for details, refer to "3. Experimental Examples" described later).
[0095] By mixing inorganic pigments in the inorganic pigment mixing process, the viscosity of the dispersion can be increased. Thus, when manufacturing the electromagnetic wave shielding sheet, the dispersion can be easily attached to the roller. The electromagnetic wave shielding sheet is manufactured by, for example, using a roll coater to attach the dispersion to a roller, and using the roller to transfer the dispersion to a substrate such as paper. If the viscosity of the dispersion is low, it will be difficult to attach the dispersion to the roller. Since the viscosity of the dispersion can be increased by mixing inorganic pigments, the dispersion can be easily attached to the roller even without using a thickener.
[0096] In addition, if the viscosity of the dispersion is to be further increased, a thickener may be mixed into the dispersion. Examples of the thickener include: celluloses such as methylcellulose and hydroxypropylcellulose, and their ammonium salts or alkali metal salts; polycarboxylates such as poly(meth)acrylic acid and modified poly(meth)acrylic acid, and their alkali metal salts; polyvinyl alcohol (co)polymers such as polyvinyl alcohol, modified polyvinyl alcohol, and ethylene-vinyl alcohol copolymers; saponified copolymers of unsaturated carboxylic acids such as (meth)acrylic acid, maleic acid, and fumaric acid and vinyl esters; and water-soluble polymers such as polyacrylamide copolymers.
[0097] In addition, the manufacture of electromagnetic wave shielding sheets is not limited to manufacture by roll coater, for example, it can also be manufactured by applying the dispersion directly to the substrate using a wire bar coater, a knife coater, an air knife coater, a blade coater, a reverse roll coater, a die coater, etc.
[0098] The viscosity of the dispersion prepared by the inorganic pigment mixing step is not particularly limited, but is preferably 100 mPa·s or more and 3000 mPa·s or less at 20°C. If the viscosity of the dispersion is 100 mPa·s or more, it is easy to apply the dispersion to the substrate using a roller as described above. Furthermore, if the viscosity of the dispersion is 3000 mPa·s or less, it is easy to eject the mixed liquid from the nozzle hole of the wet micronizing device in the above-mentioned dispersion step. The viscosity of the dispersion can be measured by a viscometer.
[0099] The dispersion prepared in the inorganic pigment mixing step may contain only CNT, inorganic pigment, CMC and water, or may contain additives in addition to CNT, inorganic pigment, CMC and water. Examples of such additives include preservatives and pH adjusters.
[0100] The mass M of CMC contained in the dispersion prepared in the inorganic pigment mixing step isCMC Relative to the sum of the mass of CNT and the mass of inorganic pigment M SUM M CMC / M SUM The ratio M in the above-mentioned mixed solution CMC / M SUM same.
[0101] 1.4. Drying process (step S4)
[0102] In the drying step, the dispersion prepared in the inorganic pigment mixing step is dried. Thus, the water in the dispersion can be evaporated to produce an electromagnetic wave shielding sheet. The method for drying the dispersion is not particularly limited, and it can be dried by a hot plate, a heater, etc., or it can be dried naturally.
[0103] In the drying step, the electromagnetic shielding sheet may be produced by placing the dispersion in a petri dish or the like and then drying the dispersion.
[0104] Alternatively, in the drying step, the dispersion may be applied to a substrate such as paper, and the applied dispersion may be dried to produce an electromagnetic wave shielding sheet. The method for applying the dispersion to the substrate is not particularly limited, and examples thereof include a method of directly applying the dispersion to the substrate using a wire bar coater, a knife coater, an air coater, a blade coater, a reverse roll coater, a die coater, etc., a method of attaching the dispersion to a roller and transferring the dispersion attached to the roller to the substrate, i.e., a so-called roll coater, etc.
[0105] 1.5. Modifications
[0106] In the above, an example is described in which the dispersion preparation process for preparing a dispersion includes a mixed liquid preparation process (step S1) of mixing CNTs, CMC and water to prepare a mixed liquid, a dispersion process (step S2) of dispersing the CNTs contained in the mixed liquid by a counter-collision method in water, and an inorganic pigment mixing process (step S3) of mixing inorganic pigments into the dispersion prepared by the dispersion process, but the dispersion preparation process is not limited to this example.
[0107] In the dispersion preparation process, for example, CNT, inorganic pigment, CMC and water may be mixed to prepare a mixed solution, and the mixed solution may be subjected to an in-water counter-collision method to disperse the CNT. Alternatively, in the dispersion preparation process, for example, an inorganic pigment powder and a CMC powder may be added to a CNT-containing liquid subjected to an in-water counter-collision method and mixed to prepare a dispersion in which CNTs are dispersed.
[0108] 2. Electromagnetic wave shielding sheet
[0109] Next, the electromagnetic wave shielding sheet of the present embodiment is described. The electromagnetic wave shielding sheet of the present embodiment is an electromagnetic wave shielding sheet manufactured by the above-mentioned "1. Method for manufacturing electromagnetic wave shielding sheet". Therefore, the electromagnetic wave shielding sheet of the present embodiment contains CNT, inorganic pigment and CMC, and the ratio of the mass of the inorganic pigment to the mass of the CNT is greater than 1 / 4 and less than 1. The electromagnetic wave shielding sheet of the present embodiment can also be composed of CNT, inorganic pigment and CMC.
[0110] The mass M of the CMC included in the electromagnetic shielding sheet of the present embodiment is CMC Relative to the sum of the mass of CNT and the mass of inorganic pigment M SUM M CMC / M SUM The ratio of M in the dispersion prepared by the inorganic pigment mixing step is CMC / M SUM The mass ratio of the components of such an electromagnetic shielding sheet can be measured by mass spectrometry.
[0111] The electromagnetic shielding sheet of this embodiment has a shape that is sufficiently large relative to its thickness in a direction perpendicular to the thickness direction. The shape of the electromagnetic shielding sheet when viewed from the thickness direction is not particularly limited, and may be a polygon such as a circle, an ellipse, or a quadrilateral.
[0112] The thickness of the electromagnetic shielding sheet of the present embodiment is not particularly limited, but is preferably 0.1 μm or more and 500 μm or less, and more preferably 1 μm or more and 300 μm or less. The thickness of the electromagnetic shielding sheet can be measured by SEM. If the thickness of the electromagnetic shielding sheet is 0.1 μm or more, the electromagnetic shielding property of the electromagnetic shielding sheet can be improved. Moreover, if the thickness of the electromagnetic shielding sheet is 500 μm or less, cracks in the electromagnetic shielding sheet can be suppressed.
[0113] The electromagnetic shielding sheet of this embodiment is not particularly limited, and has high shielding properties for frequencies above 10 MHz and below 100 GHz, for example. The shielding properties of the electromagnetic shielding sheet are evaluated by, for example, the coaxial tube method, the free space method, the microstrip line method, the KEC (Kansai Electronics Industry Promotion Center) method, etc.
[0114] 3. Experimental Examples
[0115] The present invention is described in more detail below with reference to the following experimental examples.
[0116] 3.1. Experimental Example 1
[0117] 3.1.1. Fabrication of electromagnetic wave shielding sheets
[0118] First, CNT, CMC and water were mixed to prepare a mixed solution. A homogenizer "Biomixer BM-2" manufactured by Nippon Seiki Co., Ltd. was used for the mixing. The mixing treatment time was set to 5 minutes.
[0119] The CNT used was "K-Nanos-100P" manufactured by KUMHO PETROCHEMICAL. This CNT is a MWNT with a diameter of 8nm to 15nm, a fiber length of 27μm (bundle), and a BET specific surface area of 220m 2 / g.
[0120] CMC used was "Cellogen 5A" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. The weight average molecular weight of this CMC was 11,000 to 15,000, and the degree of etherification was 0.7. Only CMC was used as a dispersant. No additives such as a thickener were added.
[0121] Next, the mixed liquid was subjected to the underwater collision method. The underwater collision method was performed using a wet micronizing device "Star Burst Labo" (model name: HJP-25005) manufactured by Sugino Machinery Co., Ltd. The diameter of the nozzle hole for spraying the mixed liquid was set to 100 μm, and the spraying pressure of the mixed liquid was set to 200 MPa. The number of times the mixed liquid passed through the wet micronizing device was set to 2 times. Thus, a dispersion containing CNT, CMC and water was prepared.
[0122] Next, an inorganic pigment was added to the above-mentioned dispersion and mixed to prepare a dispersion containing an inorganic pigment. Thus, a dispersion containing CNT, an inorganic pigment, CMC and water was prepared. In the mixing, a homogenizer "Biomixer BM-2" manufactured by Nippon Seiki Co., Ltd. was used. The mixing treatment time was set to 5 minutes.
[0123] The dispersion containing the inorganic pigment was prepared in such a manner that the ratio of the mass of CMC to the sum of the mass of the CNT and the mass of the inorganic pigment was 1 ((CNT+inorganic pigment):CMC=1:1). In addition, the dispersion was prepared in such a manner that the total content of CNT, the content of inorganic pigment and the content of CMC was 5% by mass.
[0124] In this experimental example, six kinds of inorganic pigments were used. Figure 2 is a table for explaining the inorganic pigments used in this experimental example. Figure 2 In the following, light calcium carbonate is referred to as "light calcium carbonate" and heavy calcium carbonate is referred to as "heavy calcium carbonate".
[0125] In addition, the ratio of the mass of the inorganic pigment to the mass of the CNT is adjusted to 1 / 4 to 4 (CNT:inorganic pigment=4:1 to 1:4).
[0126] The above dispersion was applied to paper ("μCoat Neos" (registered trademark) manufactured by Hokuetsu Corporation) with a basis weight of 157 g / m 2 ) and then dried at 120°C for 3 minutes to evaporate the water, thereby producing coated paper.
[0127] In the above manner, a coated paper serving as an electromagnetic shielding sheet was produced.
[0128] Furthermore, a coated paper containing no inorganic pigment was prepared. Since the coated paper contained no inorganic pigment, the CNT content was increased accordingly, and the sum of the CNT content and the CMC content in the dispersion was 5% by mass.
[0129] The dispersion was not applied to paper but placed in a petri dish and dried overnight at 50°C to evaporate water, thereby producing a dry film as an electromagnetic shielding sheet. That is, the dry film is in a state where it is not applied to a substrate such as paper.
[0130] 3.1.2. Evaluation of electromagnetic wave shielding properties
[0131] (1) Evaluation method
[0132] In the coaxial tube method, the electromagnetic shielding properties of coated paper and dry film were evaluated by measuring "S21". "S21" is equivalent to transmission loss. The larger the absolute value of "S21", the higher the electromagnetic shielding property. As the test machine, the network analyzer "ZVA67" manufactured by ROHDE & SCHWARZ and the shielding effect measurement kit "S-39D" and "S-GPC7" manufactured by KEYCOM were used. The measurement frequency was set to 45MHz to 18GHz.
[0133] (2) Evaluation results
[0134] Figure 3 This is a table showing the evaluation results of the electromagnetic wave shielding properties of coated papers. Figure 4 This is a table showing the evaluation results of the electromagnetic wave shielding properties of the dry film. Figure 3 and Figure 4 In the figure, "S21" with frequencies of 300 MHz and 7 GHz is shown. Figure 3 , Figure 4 In the following records, Figure 2"Contour1500" is called "Kaolin 1", "Hydro Gloss90" is called "Kaolin 2", "Brilliant-15" is called "Light Calcium 1", "TamaPearl TP121" is called "Light Calcium 2", "SOFTON1500" is called "Heavy Calcium 1", and "SOFTON2200" is called "Heavy Calcium 2". Figure 3 , Figure 4 In the following description, the coated paper and the dry film containing CNTs without containing an inorganic pigment are referred to as “CNTs only”.
[0135] in addition, Figure 3 The thickness of the coated paper is shown. Figure 3 In the table, "thickness" means the value obtained by subtracting the thickness of the paper as the substrate from the thickness of the entire coated paper. Figure 4 The thickness of the dried film is shown. Figure 4 In the figures, "thickness" is the thickness of the entire dry film. The thickness is measured by SEM.
[0136] in addition, Figures 5 to 10 It is a graph showing the relationship between the ratio of the mass of the inorganic pigment to the mass of the CNT and “S21”. Figure 5 This is the evaluation result of Kaolin 1. Figure 6 This is the evaluation result of Kaolin 2. Figure 7 This is the evaluation result of Light Calcium 1. Figure 8 This is the evaluation result of Light Calcium 2. Fig. 9 This is the evaluation result of heavy calcium 1. Fig.10 This is the evaluation result of heavy calcium 2.
[0137] like Figures 3 to 10 As shown in FIG. 1 , as the ratio of the mass of the inorganic pigment to the mass of the CNT increases, the absolute value of "S21" decreases. Here, as an indicator of electromagnetic wave shielding, the absolute value of "S21" is 10 dB or more when the thickness is 3 μm to 4 μm and the absolute value of "S21" is 30 dB or more when the thickness is 130 μm to 155 μm.
[0138] like Figure 3 As shown in , in coated paper, if the ratio of the mass of inorganic pigment to the mass of CNT is 1 / 4 or more and 1 or less (CNT: inorganic pigment = 1:0.25 to 1:1), the absolute value of "S21" is 10 dB or more when the thickness is 3 μm to 4 μm. Figure 4As shown in the figure, in the dry film, if the ratio of the mass of the inorganic pigment to the mass of the CNT is 1 / 4 or more and 1 or less, the absolute value of "S21" is 30 dB or more when the thickness is 130 μm to 155 μm. Therefore, it can be seen that if the ratio of the mass of the inorganic pigment to the mass of the CNT is 1 / 4 or more and 1 or less, the above-mentioned index of electromagnetic wave shielding can be met, and even if a part of the CNT is replaced by the inorganic pigment, a significant decrease in electromagnetic wave shielding can be prevented.
[0139] Moreover, if Figures 3 to 10 As shown, it can be seen that the absolute value of "S21" of kaolin 1 and 2 is larger than that of light calcium ore 1 and 2 and heavy calcium ore 1 and 2, and that an electromagnetic shielding sheet with high electromagnetic shielding property can be produced.
[0140] 3.1.3. Evaluation of film-forming properties of dried films
[0141] The film-forming properties of the dried films were evaluated. The specific evaluation criteria are as follows.
[0142] A: No cracks or ripples were generated.
[0143] B: No cracks were generated, but ripples were generated.
[0144] C: Cracks occurred.
[0145] Furthermore, "wavy" refers to a state in which the film undulates like waves although cracks are not present.
[0146] Figure 4 The evaluation results of the film-forming properties of the dried films are shown. Figure 4 As shown in the figure, kaolin 1 and 2 have better film-forming properties than light calcium 1 and 2 and heavy calcium 1 and 2. Figure 4 As shown in FIG. 1 , as the ratio of the mass of the inorganic pigment to the mass of the CNT increases, the film-forming property tends to deteriorate.
[0147] This evaluation revealed that there is a correlation between the electromagnetic wave shielding property and the film forming property, and that the better the film forming property, the higher the electromagnetic wave shielding property tends to be.
[0148] 3.2. Second Experimental Example
[0149] In the first experimental example described above, a dispersion containing an inorganic pigment was prepared. However, in the second experimental example, no inorganic pigment was used, and a dispersion containing only CNT, CMC, and water was prepared, and the dispersibility and electromagnetic wave shielding properties were evaluated.
[0150] In addition, since both CNT and inorganic pigment are inorganic materials, the evaluation results of the second experimental example can be applied to the description of the dispersibility of a dispersion liquid containing CNT, inorganic pigment, CMC and water and the electromagnetic shielding property of an electromagnetic shielding sheet manufactured from the dispersion liquid. The evaluation of the dispersibility and electromagnetic shielding property will be described below in turn.
[0151] 3.2.1. Evaluation of CNT dispersion
[0152] (1) Preparation of dispersion
[0153] CNT, CMC and water were mixed to prepare a mixed solution. The total CNT content and CMC content of the mixed solution was adjusted to 5% by mass. The ratio of the mass of CMC to the mass of CNT was adjusted to 1 / 9 to 9 (CNT:CMC=1:9 to 9:1).
[0154] Dispersions 1 to 10 were prepared in the same manner as in the above-mentioned “3.1.1. Preparation of electromagnetic shielding sheet” except for the above.
[0155] Dispersion 11 was prepared in the same manner as the above-mentioned dispersion 1 except that CMC was not mixed in the mixed solution.
[0156] Dispersion 12 was prepared in the same manner as Dispersion 4 described above except that the mixed solution was not subjected to the in-water counter-collision method. Fig.11 This is a table showing the preparation conditions of dispersions 1 to 12.
[0157] (2) Evaluation method
[0158] The dispersions 1 to 12 prepared as described above were placed in a petri dish with a diameter of 8.5 cm and dried at 50°C for 12 hours to evaporate the water. Then, the dispersion of CNT was evaluated by observing the film-forming property of the dried product. The better the dispersion of CNT, the better the uniformity of the formed film. The specific evaluation criteria are as follows.
[0159] A: A crack-free film was formed on the entire surface of the culture dish.
[0160] B: Although a film was formed on the entire surface of the culture dish, cracks were generated.
[0161] C: No film was formed.
[0162] (3) Evaluation results
[0163] Fig.11 The evaluation results of the dispersibility of dispersions 1 to 12 are shown. Fig.12 This is a photograph showing the state after dispersions 1 to 12 were placed in a petri dish and dried at 50° C. for 12 hours.
[0164] like Fig.11 and Fig.12 As shown, dispersions 1 to 8 have better film-forming properties and better CNT dispersibility than dispersions 9 to 12.
[0165] In dispersions 1 to 7, no significant difference in film-forming properties was observed, and crack-free films were formed. Dispersion 8 had cracks in the film due to the low content of CMC relative to CNT. Dispersions 9 and 10 did not form films due to the low content of CMC relative to CNT. This evaluation shows that a dispersion with good dispersibility can be prepared by setting the ratio of the mass of CMC to the mass of CNT to 1 / 7 or more, and preferably to 1 / 6 or more.
[0166] Since CMC was not added to the mixed liquid, the dispersion 11 had poor dispersibility of CNTs, and similarly to the dispersions 9 and 10 , no film was formed.
[0167] Dispersion 12 did not perform the in-water facing collision method on the mixed liquid, so the dispersibility of CNT was poor and no film was formed. It was found that by dispersing CNT by the in-water facing collision method, a dispersion with good dispersibility can be prepared.
[0168] 3.2.2. Evaluation of electromagnetic wave shielding properties
[0169] (1) Evaluation results when the ratio of CNT to CMC was changed
[0170] Coated paper was prepared from the above dispersions 1 to 12 in the same manner as in the above “3.1.1. Preparation of electromagnetic shielding sheet” Then, the electromagnetic shielding property was evaluated in the same manner as in the above “3.1.2. Evaluation of electromagnetic shielding property”.
[0171] Fig.13 This is a table showing the evaluation results of the electromagnetic wave shielding properties of coated papers. Fig.14 and Fig.15 is a graph showing "S21" with respect to frequency, Fig.13 The "S21" shown is from Fig.14 and Fig.15 The values obtained by reading 300MHz and 7GHz.
[0172] also, Fig.14 and Fig.15 is a graph showing "S21" of coated paper, Fig.14 The measurement frequency is 45MHz~3GHz, Fig.15 The measuring frequency is 500MHz~18GHz.
[0173] like Figure 13 to Figure 15As shown in the figure, in the coated paper produced from dispersions 1 to 4, the greater the CNT content, the greater the absolute value of "S21". In the coated paper produced from dispersions 4 to 7, "S21" is roughly the same. The coated paper produced from dispersions 8 to 10 has a smaller absolute value of "S21" than the coated paper produced from dispersions 4 to 7. It is conceivable that this is because dispersions 8 to 10 have poor dispersibility as described above, so the electromagnetic wave shielding property becomes lower.
[0174] This evaluation revealed that the electromagnetic shielding properties can be improved by setting the ratio of the mass of CMC to the mass of CNT to 1 / 6 or more and 3 or less (CNT:CMC=1:3-6:1), and preferably 1 / 6 or more and 1 or less (CNT:CMC=1:1-6:1).
[0175] (2) Evaluation results when the number of passes is changed
[0176] Regarding the above-mentioned dispersion 4 (CNT:CMC=1:1), the number of passes was changed by changing the treatment time of the mixed liquid by the wet micronizer, and coated paper was produced in the same manner as in the above-mentioned "(1) Evaluation when the ratio of CNT to CMC was changed". Then, the electromagnetic wave shielding property of the coated paper was evaluated. In addition, the amount of the mixed liquid was adjusted so that the treatment time of the mixed liquid by the wet micronizer for 0.5 minutes was equivalent to the number of passes of 1. Furthermore, coated paper was produced from the above-mentioned dispersion 12 (a dispersion that has not been treated by a wet micronizer) and evaluated in the same manner. Compared with a dry film, coated paper can make the CNT-containing sheet thinner, so even the dispersion 12 with poor dispersibility was successfully evaluated.
[0177] Fig.16 This is a table showing the evaluation results of the electromagnetic wave shielding properties when the number of passes was changed. Fig.17 and Fig.18 is a graph showing "S21" with respect to frequency, Fig.16 The "S21" shown is from Fig.17 and Fig.18 The values are obtained by reading 300MHz and 7GHz respectively. Fig.17 The measurement frequency is 45MHz~3GHz, Fig.18 The measuring frequency is 500MHz~18GHz.
[0178] like Figure 16 to Figure 18 As shown in FIG. 1 , the coated paper treated by the wet micronizing device has a higher electromagnetic wave shielding property than the untreated coated paper. Fig.16 As shown, the untreated coated paper has low electromagnetic wave shielding properties despite its large thickness.
[0179] This evaluation shows that the shielding properties can be improved by treating with a wet atomization device, that is, by performing the underwater counter-collision method. Figure 16 to Figure 18 Among them, no significant difference was confirmed in the electromagnetic wave shielding property of the coated paper treated by the wet micronizing device.
[0180] 3.3. Experimental Example 3
[0181] In the first experimental example, the electromagnetic wave shielding property was evaluated by the coaxial tube method, but in the third experimental example, the electromagnetic wave noise suppression performance was evaluated by the microstrip line method. The coated paper containing the inorganic pigment produced by the first experimental example was evaluated. As the test machine, the network analyzer "ZVA67" manufactured by ROHDE & SCHWARZ and the test fixture "TF-18C" manufactured by KEYCOM were used. The measurement frequency was set to 500MHz to 18GHz.
[0182] Fig.19 TABLE 2 is a table showing the evaluation results of the electromagnetic wave noise suppression performance of coated paper, showing "Rtp" at 6 GHz and 15 GHz. "Rtp" represents the transmission attenuation rate, and the larger the absolute value, the higher the electromagnetic wave noise suppression performance.
[0183] Figure 20 to Figure 25 is a graph showing "Rtp" relative to frequency, Fig.19 The "Rtp" shown is from Figure 20 to Figure 25 The values at 6 GHz and 15 GHz are obtained. Fig. 20 The case where the ratio of the inorganic pigment to the CNT (hereinafter also referred to as “inorganic pigment ratio”) is 0.25 is shown. Fig.21 The case where the inorganic pigment ratio is 0.5 is shown. Fig. 22 The case where the inorganic pigment ratio is 1.0 is shown. Fig.23 The case where the ratio of the inorganic pigment is 2.0 is shown. Fig.24 The case where the inorganic pigment ratio is 3.0 is shown. Fig.25 The case where the ratio of the inorganic pigment is 4.0 is shown.
[0184] like Fig. 20 As shown in FIG. 1 , when the inorganic pigment ratio is “0.25”, the “Rtp” of kaolin 1 and 2 is larger than that of light calcium 1 and 2 and heavy calcium 1 and 2. Fig.19 As shown, the kaolins 1 and 2 having an inorganic pigment ratio of "0.25" have larger "Rtp" at 6 GHz than the kaolins 1 and 2 having an inorganic pigment ratio of "0.5" to "4.0".
[0185] Among all the inorganic pigments, the "Rtp" at 15 GHz was larger when the inorganic pigment ratio was "0.5", "1.0" and "2.0" than when the inorganic pigment ratio was "0.25", "3.0" and "4.0".
[0186] The above-mentioned embodiments and modifications are merely examples, and the present invention is not limited thereto. For example, each embodiment and each modification may be appropriately combined.
[0187] The present invention is not limited to the above-mentioned embodiments, and various modifications can be further made. For example, the present invention includes a configuration that is substantially the same as the configuration described in the embodiment. The so-called substantially the same configuration refers to, for example, a configuration with the same function, method and result, or a configuration with the same purpose and effect. In addition, the present invention includes a configuration in which a non-essential part of the configuration described in the embodiment is replaced. In addition, the present invention includes a configuration that has the same effect as the configuration described in the embodiment, or a configuration that can achieve the same purpose. In addition, the present invention includes a configuration in which a known technology is added to the configuration described in the embodiment.
Claims
1. A method for manufacturing an electromagnetic wave shielding sheet, characterized in that: Include: A step of preparing a dispersion containing carbon nanotubes, an inorganic pigment, sodium carboxymethyl cellulose and water; and a step of drying the dispersion, The process of preparing the dispersion comprises: a step of mixing the carbon nanotubes, the sodium carboxymethyl cellulose and the water to prepare a mixed solution, In the mixed liquid, the content of the carbon nanotubes is 0.1 mass % or more and 3.0 mass % or less, In the dispersion, a ratio of the mass of the inorganic pigment to the mass of the carbon nanotubes is 1 / 4 or more and 1 or less, In the dispersion, a ratio of the mass of the sodium carboxymethyl cellulose to the sum of the mass of the carbon nanotubes and the mass of the inorganic pigment is 3 or less.
2. The method for producing an electromagnetic shielding sheet according to claim 1, wherein: The inorganic pigment is kaolin.
3. The method for producing an electromagnetic shielding sheet according to claim 1 or 2, wherein: In the process of preparing the dispersion, only the sodium carboxymethyl cellulose is used as a dispersant.
4. The method for producing an electromagnetic shielding sheet according to claim 1 or 2, wherein: The process of preparing the dispersion comprises: A step of dispersing the carbon nanotubes contained in the mixed solution by a counter-collision method in water.
5. An electromagnetic wave shielding sheet, characterized in that , An electromagnetic shielding sheet manufactured by the method for manufacturing an electromagnetic shielding sheet according to any one of claims 1 to 4.
Citation Information
Patent Citations
Carbon nanotube aqueous dispersion and composite sheet obtained by using the same
JP2013082610A
High elastic aqueous conductive nano coating
CN101353547A
Anti-Static Articles and Materials
US20150284141A1